2007
DOI: 10.2298/jsc0704367g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of some new coordination compounds of boron with mixed azines

Abstract: Some new boron complexes have been synthesized by the reaction of triisopropohxyborane with the mixed azines, prepared by the condensation of salicylaldehyde and hydrazine with aldehydes/ketones in a 1:1:1 mole ratio to give a new series of (OPr i ) 2 B(NO) type of complexes. Their structures were confirmed on the basis of elemental analyses, ultraviolet, infrared, 1 H-NMR and 11 B-NMR spectral studies. The ligands and their boron complexes were also screened for their antifungal activity. Several of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Cresswell et al [19] have reported that Boron was more inhibitory than Cu to mycelia growth of Agaricus biosporus. The radial growth of pathogenic fungi Pyricularia oryzae, Fusarium oxysporum and Aspergillus niger was reduced by the activity of Boron [20]. Chowdhury [21] observed that the use of Boron reduced the growth of Macrophomina phaseolina.…”
Section: Effect Of Boron (Boric Acid) On Growth and Sclerotia Formatimentioning
confidence: 99%
“…Cresswell et al [19] have reported that Boron was more inhibitory than Cu to mycelia growth of Agaricus biosporus. The radial growth of pathogenic fungi Pyricularia oryzae, Fusarium oxysporum and Aspergillus niger was reduced by the activity of Boron [20]. Chowdhury [21] observed that the use of Boron reduced the growth of Macrophomina phaseolina.…”
Section: Effect Of Boron (Boric Acid) On Growth and Sclerotia Formatimentioning
confidence: 99%
“…The use of azines as starting materials in organic synthesis is well documented. 31 These readily available compounds have been widely used as substrates in the synthesis of substituted hydrazones 62 and heterocyclic compounds 37 such as pyrazoles, purines, and pyrimidines. [63][64][65][66] As dipolarophils, they can undergo 1,3-cycloadditions and thus provide an efficient route to afford 1,5-diazabicyclo[3.3.0]octanes by crisscross addition.…”
Section: Chemical Applicationsmentioning
confidence: 99%
“…The AIE (E) characteristics have been a great potential for the development of distinct optical applications, from sensing to light emitting devices. [ 12 ] Besides, AIE azines are having fascinating physical and chemical properties, azines and their derivatives have been extensively used in dyes,[ 13 ] biological,[ 14 ] pharmaceutical,[ 15 ] nonlinear optical fluorophores,[ 16, 17 ] design of liquid crystals,[ 18 ] as ligands for the synthesis of novel organometallic compounds [ 19 ] and other material applications. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%